Ethnobotanical approaches to anorectal disorders in tribal communities of Chhattisgarh, Central India - Bhoi, Diptesh; Jangde, Reshma; Kumar, Roshan; Patel, Ashvani; AHIRWAR, RAMESH KUMAR (Ethnobotany Research and Applications, 2025)
Background: The Indian state of Chhattisgarh, known for its rich forest biodiversity and traditional medicinal knowledge, has a long-standing heritage of using plants to treat various ailments. However, no ethnobotanical study has specifically focused on the treatment of haemorrhoids in this region. This study was conducted to document the medicinal plants used by traditional healers in the Surguja district for haemorrhoid treatment. Methods: Ethnobotanical data were collected from 22 traditional healers across 11 villages in the Ambikapur, Mainpat, and Udaipur blocks of Surguja district through semi-structured interviews. Use Value (UV), Fidelity Level (FL), and Jaccard Index (JI) were calculated to assess cultural importance, consensus, and regional similarity. Results: A total of 47 plant species, belonging to 44 genera and 33 families, were recorded for the treatment of haemorrhoids and other ailments. UV values ranged from 0.23 to 1.36, with Achyranthes aspera L. and Aegle marmelos (L.) Corrêa showing the highest UV (1.36), followed by Asparagus racemosus Willd., Calotropis procera (Aiton) W.T.Aiton, and Tinospora crispa (L.) Hook. f. & Thomson (UV = 1.27). FL ranged from 11.76% to 80%, with the highest value recorded for Musa × paradisiaca L. and Cynodon dactylon (L.) Pers. (80%). The highest similarity (8.57%) was observed with ethnobotanical data from Manipur. Conclusion: This study is the first to report medicinal plant use for haemorrhoid treatment in Chhattisgarh. Several species showed high cultural value and are recommended for further phytochemical, pharmacological, and in silico investigations to explore their therapeutic potential. Keywords: Ethnobotany, Haemorrhoids, Medicinal Plants, Traditional Healers, Use Value